"To Understand the Place": Geographical Knowledge and Diplomatic Practice. Issue 4 (1st October 2016) - Kuus, Merje
Abstract : Diplomats produce a great deal of geographical knowledge: By reporting on distant places to their governments, they create particular understandings of political space. Yet these professionals rarely link their work to geography: What a geographer might call a geographical sensibility is labeled cultural knowledge by a diplomat. This article clarifies the relationship between geographical knowledge and diplomatic practice. Empirically, it draws from nearly 100 interviews with foreign policy professionals to offer a more "peopled" or quasi-ethnographic account of diplomacy than is usually available in scholarly literature. Conceptually, the article contributes to our understanding of how geographical knowledge is created inside diplomatic and bureaucratic institutions.